2014
DOI: 10.1002/jso.23829
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of mastectomy patients with and without delayed breast reconstruction: Long‐term psychosocial functioning in the breast cancer survivorship period

Abstract: Psychosocial functioning improves over time in patients treated with mastectomy in the long-term breast cancer survivorship period, which may be related to the effect of time post-treatment, rather than an effect of choice for or against DBR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…2 Receiving the diagnosis of breast cancer is something that generates transformations in a woman's life, since the breasts are important for the female self-image. The breasts refer women to their femininity, sexuality and fertility.…”
Section: Emotional Issues After Mastectomymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Receiving the diagnosis of breast cancer is something that generates transformations in a woman's life, since the breasts are important for the female self-image. The breasts refer women to their femininity, sexuality and fertility.…”
Section: Emotional Issues After Mastectomymentioning
confidence: 99%
“…The feelings associated with this picture are of vulnerability, sadness and fear. 2,3,4 In the age of imaging and oncoplastic examinations, mutilating surgeries are no longer justified in the vast majority of cases of breast cancer, since issues relating to aesthetics and patients' mental health are present throughout the course of treatment. Failure to identify and Am In.…”
Section: Emotional Issues After Mastectomymentioning
confidence: 99%
“…Этим данным противоречат результаты проведенного на протяжении 2 лет иссле-дования -уровни депрессии и тревоги у 258 больных РМЖ, перенесших РМЭ, РМЭ с реконструкцией и ра-дикальную резекцию (РР), были аналогичными [19]. Изучение психоэмоционального состояния 39 боль-ных РМЖ, перенесших РМЭ, и 28 больных, которым была произведена отсроченная реконструкция молоч-ной железы, показало ослабление на протяжении 1-6 лет признаков дистресса у всех пациенток, однако общий индекс тяжести дистресса был выше у послед-ней группы [20]. Качество жизни, связанное со здоро-вьем, с учетом психоэмоциональной сферы, по дан-ным [21], было выше у больных РМЖ, перенесших органосохраняющие операции, по сравнению с пере-несшими РМЭ с реконструкцией и без, а по данным [22,23] -у пациенток, перенесших РМЭ с одномо-ментной реконструкцией молочной железы.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified
“…Other studies have concluded that differences in body satisfaction and psychosocial outcomes in women who do and do not reconstruct their breast(s) are not significant over time (Rowland et al, 2000;Metcalfe et al, 2012 ). A recent longitudinal study in Canadian women showed women who had DBR reported significantly higher levels of obsessiveness and cancer-related distress compared with those with mastectomy alone; no differences in quality of life were evident between the groups over time (Metcalfe et al, 2015). Statistics delineating reconstruction rates by age are not readily available in the UK, but data from the US indicate that BR rates are increasing and younger women are more likely to select reconstruction (Jagsi et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The complexity of body image negotiation with women who have opted for BR has been documented (Crompvoets, 2006;Reaby et al, 1994, Rubino et al, 2007Fallbjork et al, 2012;Metcalfe et al, 2015;Grogan and Mechan, 2016); however, very little to date has highlighted the experiences of women who opt not to pursue IBR or DBR (Authors, 2014). In their study with younger women with and without BR post-mastectomy, Grogan and Mechan (2016) found that positive framing of scars and rejection of Western beauty ideals was instrumental to the increased self-efficacy of some of their participants.…”
mentioning
confidence: 99%